Antitumor Cell-Complex Vaccines Employing Genetically Modified Tumor Cells and Fibroblasts - Antonio Miguel; María José Herrero; Luis Sendra; Rafael Botella; Ana Diaz; Rosa Algás; Salvador F. Aliño (Toxins, 2014)
The present study evaluates the immune response mediated by vaccination with cell complexes composed of irradiated B16 tumor cells and mouse fibroblasts genetically modified to produce GM-CSF. The animals were vaccinated with free B16 cells or cell complexes. We employed two gene plasmid constructions: one high producer (pMok) and a low producer (p2F). Tumor transplant was performed by injection of B16 tumor cells. Plasma levels of total IgG and its subtypes were measured by ELISA. Tumor volumes were measured and survival curves were obtained. The study resulted in a cell complex vaccine able to stimulate the immune system to produce specific anti-tumor membrane proteins (TMP) IgG. In the groups vaccinated with cells transfected with the low producer plasmid, IgG production was higher when we used free B16 cell rather than cell complexes. Nonspecific autoimmune response caused by cell complex was not greater than that induced by the tumor cells alone. Groups vaccinated with B16 transfected with low producer plasmid reached a tumor growth delay of 92% (p ≤ 0.01). When vaccinated with cell complex, the best group was that transfected with high producer plasmid, reaching a tumor growth inhibition of 56% (p ≤ 0.05). Significant survival (40%) was only observed in the groups vaccinated with free transfected B16 cells.